Variasi Pemakaian Bahasa Manggarai Desa Golo Sengang Kecamatan Sano Nggoang Kabupaten Manggarai Barat - Marifa, Sia; Rismarini Nursaly, Baiq; Taufiq, Muh. (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
The aim of this research is to analyze and describe the variety of uses of the Manggarai language in Golo Sengang Village, West Manggarai. This research also wants to know the influence of the environment and community habits on the differences in language used in daily interactions. This research is a qualitative description. Data was collected through direct observation and interviews with local residents. Observations were carried out by being directly involved in the conversation, recording the conversation, and noting important things. The results of the research showed that there were variations in the use of words that were typical for certain individuals (idiolects) such as hau, ite, and met, as well as the use of different words. based on social status (sociolect) such as father, mother and mother. Apart from that, there are also variations in language use in agricultural and trade contexts, such as the words mawo (possibly meaning plant), woja (possibly meaning agricultural tools), and market.